The Persistence of Ethnocentric Framing in Online News Coverage of European Politics. Issue 3 (15th March 2020) - Trimithiotis, Dimitris
Abstract: This article explores the potential added value of online news media in reporting European Union (EU) politics. Precisely, it examines the extent to which online reporting could generate more prominent, more pluralistic and less ethnocentric coverage of EU politics. The above issue is scrutinised in the Cypriot context. A context where the economic crisis has negatively affected both the working conditions in newsroom and the public opinion on EU. The study is based on a corpus of news reports delivered by online news media that vary regarding their journalistic culture, political identity, organisational structure and volume and degree of establishment. Drawing on a multi-method research design, this article argues that online news media in Cyprus do not make effective use of online medium in favour of more prominent, comprehensive and pluralistic reporting. Instead, they exploit the online potential for decreasing their investment in both personnel and time for the coverage of "not so important" topics as EU politics. The article highlights how journalistic processes of news production and journalism culture in synergy with digitalisation processes contribute to the persistence of narrow coverage and ethnocentric framing of EU news.